2004
DOI: 10.1074/jbc.m306653200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Presenilin 1 at the Caspase Recognition Site Regulates Its Proteolytic Processing and the Progression of Apoptosis

Abstract: The Alzheimer's disease-associated presenilin (PS) 1 is intimately involved in ␥-secretase cleavage of ␤-amyloid precursor protein and other proteins. In addition, PS1 plays a role in ␤-catenin signaling and in the regulation of apoptosis. Here we demonstrate that phosphorylation of PS1 is regulated by two independent signaling pathways involving protein kinase (PK) A and PKC and that both kinases can directly phosphorylate the large hydrophilic domain of PS1 in vitro and in cultured cells. A phosphorylation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 63 publications
2
45
0
Order By: Relevance
“…2B). The weak phosphorylation of the S353D/S357D mutant is consistent with additional phosphorylation sites in the PS1 CTF besides Ser 353 and Ser 357 (15,31,32). Cell treatment with a GSK3␤ inhibitor decreased the phosphorylation of PS1-wt, but had little effect on that of PS1-S353D/S357D, indicating an involvement of GSK3␤ in the in vivo phosphorylation of PS1 at Ser 353 and Ser 357 (Fig.…”
Section: Gsk3␤ Phosphorylates the Ps1 Hydrophilic Loop At Positions 3supporting
confidence: 67%
“…2B). The weak phosphorylation of the S353D/S357D mutant is consistent with additional phosphorylation sites in the PS1 CTF besides Ser 353 and Ser 357 (15,31,32). Cell treatment with a GSK3␤ inhibitor decreased the phosphorylation of PS1-wt, but had little effect on that of PS1-S353D/S357D, indicating an involvement of GSK3␤ in the in vivo phosphorylation of PS1 at Ser 353 and Ser 357 (Fig.…”
Section: Gsk3␤ Phosphorylates the Ps1 Hydrophilic Loop At Positions 3supporting
confidence: 67%
“…However, when we performed restoration experiments for the defective PS-1 mutants, it was of great interest to find that their endoproteolyzed forms, NTF and CTF, had different effects on restoring the defective PS-1 mutants with regard to Notch cleavage. To date, NTF is known to interact with Pen-2, whereas CTF interacts with Nicastrin (45) and contains a caspase recognition site (43). The CTF of PS-2 has been shown to affect apoptosis (46), but the different biological functions and regulation of NTF and CTF have not been clearly documented yet.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of PS1 at Ser397 by GSK3β (91) and at Thr354 by P35/ Cdk5 residue (17) regulates C-terminal fragment stability. PKA-mediated phosphorylation strongly inhibits proteolytic processing of PS1 by caspase activity during apoptosis, reducing the progression of apoptosis (92). Recent studies have shown that ERK1/2 is an endogenous negative regulator of γ-secretase, potentially through the direct phosphorylation of Nicastrin (93).…”
Section: Phosphorylation Of Presenilin-containing γ-Secretase Complexmentioning
confidence: 99%